Morphological impact of insulator on inkjet-printed transistor. (28th September 2017) - Moon, Sjeung Jae; Robin, Malo; Wenlin, Kuai; Yann, Molard; Bae, Byung Seong; Mohammed-Brahim, Tayeb; Jacques, Emmanuel; Harnois, Maxime
Abstract: This study reports on the impact of electrodes (source and drain) and the insulator cross-sectional profile on the electrical behavior of printed organic field effect transistors (OFETs). Varying processing techniques, from classical lithography to inkjet printing, show different cross-sectional profiles. Indeed, due to the coffee stain effect (usually considered a drawback), the inkjet-printed insulator shows a wave-shaped profile although the spin-coated one is perfectly smooth. However, OFET electrical behavior is not drastically impacted by the insulator cross-sectional profile. Moreover, this study clearly demonstrates that independently of the insulator cross-sectional profile, OFETs fabricated with printed electrodes show the worst electrical characteristics. Consequently, this work clearly demonstrates that a challenging issue for the fabrication of efficient fully-printed OFETs relies on drain and source optimization (for instance, morphology or material).